PENDIDIKAN JIHAD DALAM ISLAM - Hasiah, HAsiah (AIN Padangsidimpuan, 2013)
AbstractMisundertand about jihad as one violence, battle terror, bombardiment to begin event that to do group to name moeslem jihad as. activity that inclined meaning fisik very stain image moeslem. As bring rahmad imflicution negative not other only one load psikiologis– historis that to add problem yet. Struggle do seriously, diligent, steady and. Not dissapoited mentioned also jihad.Keyword: Pendidikan Jihad, Islam